The role of hospital performance assessment on medical tourism development - Mona Mohammadnia; Kamran Hajinabi; Mahmoud Mahmoudi Majd Abadi; Ali Komeli (Journal of Biostatistics and Epidemiology, 2018)
Background & Aim- Medical tourism industry would not be developed without well-known healthcare centers which popular for their therapeutic outcome, efficiency, patient centeredness, responsive to governance and staff orientation. To do so, this study designed and carried out. Materials & Methods- This was an applied, correlation and cross-sectional study which was done in first quarter of 2018. The population of study consisted of International patient department hospitals staff that were selected randomly (N=263). There were used two kinds of research-made questionnaires for medical tourism development and hospital performance assessment which were included of 14 and 45 questions respectively and validated by experts. The reliabilities determined as 0.85 for medical tourism development and 0.68 for hospital performance assessment by Cronbach’s alpha coefficient .The Pearson correlations counted as 0.85. SPSS version 21 was used for all descriptive and inferential analysis. Results- It has been shown that there was a significant correlation between all hospital performance assessment dimensions and medical tourism industry (P<0.05). The most correlation related to patient centeredness (r=0.45) and the least went to staff orientation (r=0.30). Total amount of correlation between two variables determined as 0.76. Conclusion- There was a significant and direct relation between hospital performance assessment dimensions and medical tourism development. So, it is strongly recommended that hospital managers as well as policy makers implement hospital performance strengthening strategies for generating medical tourism attraction.